Numerical Design of RF Antennas for Ion Cyclotron Resonance Heating in ECRIS Environment. Issue 1 (1st April 2022) - Mauro, G. S.; Torrisi, G.; Pidatella, A.; Galatá, A.; Mascali, D.
Abstract: In this paper we present the numerical design and simulation of RF antennas to be employed in Ion Cyclotron Resonance Heating (ICRH) systems working in ECRIS environment. A 3D full-wave numerical model, based on the coupling between COMSOL FEM solution of Maxwell equations and the MATLAB-computed non-homogeneous plasma dielectric tensor, has been employed in order to study the performances of several ICRH antennas. Results in terms of S-parameters, on-axis electric field and RF absorbed power inside the plasma chamber have been obtained and compared between the chosen antenna geometries. The presented study will permit to better understand the fundamental aspects of ion dynamics in ECRISs as well as allowing the design of a proper matching network between the RF amplifier and the antenna, necessary to cope with the plasma properties' fast variations. Further ion kinetic simulations are ongoing.